Trends in the Lethality of American Violence. Issue 3 (August 2019) - Berg, Mark T.
Research on homicide trends has not adequately considered trends in interpersonal disputes. Aggregate homicide rates partly reflect the extent to which less serious forms of interpersonal violence escalate to deadly violence. This study argues that the rate of disputes in a society and the proportion that result in deadly violence vary independently. But both are necessary to understand lethality trends. The study compares rates of homicide in the Supplemental Homicide Report with rates of violence in the National Crime Victimization Survey to estimate lethality trends from 1992 to 2016. Findings are discussed regarding their implications for explanations of homicide trends.